Obacunone Retards Renal Cyst Development in Autosomal Dominant Polycystic Kidney Disease by Activating NRF2 - Zhiwei Qiu; Jinzhao He; Guangying Shao; Jiaqi Hu; Xiaowei Li; Hong Zhou; Min Li; Baoxue Yang (MDPI AG, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is a common inherited disease characterized by progressive enlargement of fluid-filled cysts derived from renal tubular epithelial cells, which has become the fourth leading cause of end-stage renal diseases. Currently, treatment options for ADPKD remain limited. The purpose of this study was to discover an effective therapeutic drug for ADPKD. With virtual screening, Madin-Darby canine kidney (MDCK) cyst model, embryonic kidney cyst model and kidney-specific Pkd1 knockout mouse (PKD) model, we identified obacunone as a candidate compound for ADPKD drug discovery from a natural antioxidant compound library. In vitro experiments showed that obacunone significantly inhibited cyst formation and expansion of MDCK cysts and embryonic kidney cysts in a dose-dependent manner. In vivo, obacunone treatment significantly reduced the renal cyst development in PKD mice. Western blot and morphological analysis revealed that obacunone served as a NRF2 activator in ADPKD, which suppressed lipid peroxidation by up-regulating GPX4 and finally restrained excessive cell proliferation by down-regulating mTOR and MAPK signaling pathways. Experimental data demonstrated obacunone as an effective renal cyst inhibitor for ADPKD, indicating that obacunone might be developed into a therapeutic drug for ADPKD treatment.